Analyzing promotions of racial/ethnic minority CEOs. Issue 4 (6th May 2014) - Cook, Alison; M. Glass, Christy
Abstract : Purpose: – The purpose of this paper is to understand the conditions under which racial/ethnic minorities are promoted to top leadership positions in American corporations. In addition to testing the glass cliff theory for racial/ethnic minorities, the paper also develops and test two additional theoretical mechanisms: bold moves and the savior effect. While the glass cliff theory predicts racial/ethnic minorities will be promoted to struggling firms, the bold moves theory predicts the opposite, that racial/ethnic minorities will be promoted to strong firms. The savior effect predicts that minority CEOs will be replaced by white male leaders if firm performance struggles during their tenure. Design/methodology/approach: – This paper relies on conditional logistic regression to analyze all CEO transitions among Fortune 500 companies over a 15-year period. Findings: – Consistent with the bold moves thesis but contrary to the predictions of glass cliff theory, the results suggest that racial/ethnic minorities are more likely than white executives to be promoted CEO in strongly performing firms. As predicted by the savior effect theory, the paper also finds that when firm performance struggles under the leadership of racial/minority CEOs, these leaders are likely to be replaced by white CEOs. Research limitations/implications: – The findings contradict theory of the glass cliff and suggest additional mechanisms that shape the promotion probability of minority leaders. Practical implications: – Race and ethnicity shape promotion and replacement decisions for top leadership positions in important ways. While minority leaders are not set up to fail, as glass cliff theory would predict, the authors do find that confidence in the leadership of minority leaders may be tenuous. To overcome the risks of replacement of minority leaders, firms should seek to eliminate bias by allowing minority leaders enough time and resources to overcome declines in firm performance and increase the transparency of replacement decisions. Originality/value: – This is one of the first studies to test the glass cliff thesis with regard to racial/ethnic minorities. The paper also develops and tests two new mechanisms related to leader succession: bold moves and the savior effect.